Development and application of a new Forestation Index: global forestation patterns and drivers - Zsófia Benedek; Imre Fertő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Deforestation has long been heavily studied; several proximate and underlying causes behind the global decrease of forest extent have been discussed. However, systematic analyses of positive examples are sparse, even if forestation is happening in almost 70 countries (on approximately 40% of the world forested area). This study focuses on countries where forest cover increased between 1990 and 2010. As "forests" is a heterogeneous group, a biodiversity-corrected Forestation Index is also introduced to distinguish between different forms of "environmentally valuable" new forests (that are expected to have positive impact on biodiversity) and monocultures (that are debatable with that respect). OLS regression is used to reveal factors that may influence the observed patterns. Our results present some evidence to support the existence of an environmental Kuznets curve (EKC). Direct conservation investments appear to have negative effect on forestation which implies substitution of measures. Several traditional factors, which are important in deforestation (such as corruption, economic freedom, etc.) seems to have no impact from forestation perspective. Results show that refinement is needed during the modelling of forestation and different types should be acknowledged - treatment of forests as a homogenous category is an oversimplification.
Keywords: Q23; Q56; Q57; 330; Forests; biodiversity; global model; environmental Kuznets curve; environmental policy